2012
DOI: 10.1017/s1368980012004545
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic factors and risk-taking behaviour during adolescence and obesity among more than 40 000 Danes

Abstract: Objective: The prevalence of obesity has increased in the last decades in the Western world. The aim of the present study was to examine the association between risk-taking behaviour in adolescence and adult obesity in men and women. Furthermore, we wished to describe social differences in obesity in Denmark. Design: Two population-based questionnaire studies (2004-2005 and 2006-2007) were used to collect information on weight and height, sociodemographic factors and factors regarding risk-taking behaviour d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
2
5
0
1
Order By: Relevance
“…Incorrect dietary habits and low physical activity, which depend on individual health choices, are the most important risk factors for overweight and obesity [1][2][3][4][5]. However, numerous studies underline the relationship between overweight/obesity and sociodemographic status [3][4][5]20,21,38,39]. Financial situation, educational level and occupational status are considered as the most important sociodemographic factors which contribute to overweight/obesity [38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorrect dietary habits and low physical activity, which depend on individual health choices, are the most important risk factors for overweight and obesity [1][2][3][4][5]. However, numerous studies underline the relationship between overweight/obesity and sociodemographic status [3][4][5]20,21,38,39]. Financial situation, educational level and occupational status are considered as the most important sociodemographic factors which contribute to overweight/obesity [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant gap in nationwide representative studies on nutritional statuses in different socio-economic groups in Poland. Data from other countries indicate that sociodemographic factors may influence the risk of overweight and obesity [20,21]. It is particularly important to investigate the relationship between these factors and overweight and obesity in Poland due to significant changes in inter alia, age structure, level of education, and economic situation in recent years [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of obesity is increasing worldwide . In Denmark, the prevalence of obesity has exhibited a marked increase within the past 25 to 30 years, particularly for reproductive‐aged women, of whom 9.7% were obese in 2006–2007 . Studies have reported that both obesity and underweight are associated with an increased risk of spontaneous abortion (SAB).…”
mentioning
confidence: 99%
“…Mevcut çalışmada ele alınan medeni durum değişkenine göre duygusal yeme farklılıklarıyla ilgili olarak literatürde benzer örneklem grubu üzerinde çalışmalara rastlanmamıştır. Ancak sağlık bilimleri alanında yapılan çalışmalarda evli bireylerin evli olmayanlara göre obez olma durumlarının daha fazla olduğu görülmüştür (İpek, 2019;Janghorbani vd., 2008;Frederiksen, 2014;Hanson vd., 2007;Tzotzas vd., 2003). Sosyal görünüş kaygısının medeni duruma göre incelendiği çalışmalara bakıldığında Erdoğan (2021), sosyal görünüş kaygısının medeni duruma göre farklılaştığı, evlilerde sosyal görünüş kaygısının bekârlara oranla daha yüksek olduğu sonucuna ulaşmıştır.…”
Section: Tartışma Ve Sonuçunclassified